(untitled) (Tanzania Journal for Population studies and Development, 2024)
Nigeria ranks high in maternal mortality among developing countries despite the effort to reduce it. This paper is based on a ten-year study from 2008 to 2017 on maternal mortality from two public healthcare facilities in Edo State that have the most referrals. A facility-based survey design was used to determine the maternal mortality ratio, level of obstetric utilisation (booked and un-booked patients), number of caesarean sections, and causes of maternal deaths. Information on maternal deaths was collected from the University of Benin Teaching Hospital and the Central Hospital. The number of maternal deaths was 350 with 54,124 live births; and the Maternal Mortality Ratio (MMR) was 674 per 100,000 live births during this ten-year review. The findings show an increase of 11,780 caesarean sections among pregnant women during the delivery period. The major direct causes of maternal death were eclampsia and haemorrhage, while the indirect causes were HIV/AIDS, and other complications. The high number of pregnant women with no antenatal registration (un-booked) in these facilities depicts delays in receiving effective maternal healthcare services. The need arises for early registration and basic/comprehensive emergency obstetric care (EMOC) at all tiers of health facilities, which will decrease the risk of mortality and morbidity. The study recommends that to prevent delays in offering maternal healthcare services, there should be effective EMOCs at all healthcare facilities, and there is a need to encourage early antenatal registration that could reduce caesarean sections at health facilities for most pregnant women.